Collective constructions of ‘waste’: epistemic practices for disinvestment in the context of Dutch social health insurance - Floortje Moes; Eddy Houwaart; Diana Delnoij; Klasien Horstman (BMC Health Services Research, 2019)
Abstract Background Faced with growing budget pressure, policymakers worldwide recognize the necessity of strategic disinvestment from ineffective, inefficient or harmful medical practices. However, disinvestment programs face substantial social, political and cultural challenges: mistrust, struggles for clinical autonomy or stakeholders’ reluctance to engage in what can be perceived as ‘rationing’. Academic literature says little about effective strategies to address these challenges. This paper provides insights on this matter. We analyzed the epistemic work of a group of policymakers at the National Health Care Institute on what was initially a disinvestment initiative within the context of the Dutch basic benefits package: the ‘Appropriate Care’ program. The Institute developed a strategy using national administrative data to identify and tackle low-value care covered from public funds as well as potential underuse, and achieve savings through improved organization of efficiency and quality in health care delivery. How did the Institute deal with the socio-political sensitivities associated with disinvestment by means of their epistemic work? Method We conducted ethnographic research into the National Health Care Institute’s epistemic practices. Research entailed document analysis, non-participant observation, in-depth conversations, and interviews with key-informants. Results The Institute dealt with the socio-political sensitivities associated with disinvestment by democratizing the epistemic practices to identify low-value care, by warranting data analysis by clinical experts, by creating an epistemic safe space for health care professionals who were the object of research into low-value care, and by de-emphasizing the economization measure. Ultimately, this epistemic work facilitated a collaborative construction of problems relating to low-value care practices and their solutions. Conclusions This case shows that – apart from the right data and adequate expertise – disinvestment requires clinical leadership and political will on the part of stakeholders. Our analysis of the Institute’s Appropriate Care program shows how the epistemic effort to identify low-value care became a co-construction between policymakers, care providers, patients and insurers of problems of ‘waste’ in Dutch social health insurance. This collective epistemic work gave cognitive, moral and political standing to the idea of ‘waste’ in public health expenditure.